Community Memories : A Glimpse of African American Life in Frankfort, Kentucky - Fletcher, Winona L.; Hardin, John; Boyd, Douglas A., 1970-; Winter, Mary E., 1953-; Wallace, James E., 1957-; Burton, Sheila Mason, 1948- (Book collections on Project MUSE., 2003)
"While this is a glimpse of Frankfort's African American community, it has much in common with other Black communities, especially those in the South. Although much in the collection that produced this work - both photographic and oral history - is nostalgic, it ultimately demonstrates that change is constant, producing both negative and positive results."--Jacket